Solar cell fine grid slurry and preparation method and application thereof

By using nano silver powder and micro silver powder in the fine grid slurry of solar cell, combined with specific resin and solvent formulas, the thixotropy and ink permeability of the slurry are optimized, and the problem of excellent ink permeability in the printing process of full-open steel plate is solved, efficient printing is achieved and the conversion efficiency and yield of the battery is improved.

CN119650134APending Publication Date: 2025-03-18FOSHAN HAOYU XINNENG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411885103.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, when preparing the fine grid slurry of solar cells, it is difficult to effectively solve the problem of excellent ink transmission effect during the printing process of full-open steel plates, resulting in submersion phenomenon and uneven thickness of fine grid lines, affecting the conversion efficiency and yield of the battery.

Method used

By using a combination of nano-silver powder and micro-silver powder in fine-gate slurry, combined with specific resin and solvent formulations, the thixotropy and ink permeability of the slurry are optimized to match the design requirements of fully-opened steel plates.

Benefits of technology

The smooth printing of fine grid slurry when the fully-opened steel plate design opening is 10μm, reducing the number of EL grid breaks and improving the conversion efficiency and yield of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic electronic paste, in particular to solar cell fine grid paste and a preparation method and application thereof. The fine grid slurry comprises the following components: metal powder, glass powder, an organic carrier, a plasticizer and an organic auxiliary agent, the addition amount of the metal powder in the fine grid slurry is 80-95 wt%, the metal powder comprises nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1: (3-10). The fine grid slurry can be smoothly printed when the opening of a full-opening steel plate is designed to be 10 microns, the problem of poor material spreading caused by the mirror surface of the full-opening steel plate is solved, the viscosity of the fine grid slurry is improved, and meanwhile the ink penetration effect of the fine grid slurry can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic electronic pastes, and in particular to a solar cell fine grid paste and a preparation method and application thereof. Background Art

[0002] Since the large-scale production of crystalline silicon solar cells, screen printing technology has been often used to prepare electrodes, but the screen woven with steel wire mesh has knots, which can easily lead to blockage and EL (full name electroluminescence) broken grid problems, affecting production capacity, yield and conversion efficiency. The current conventional screen opening design is between 25-30μm, but the design below 20μm is extremely difficult, and the finer fine grid opening combined with high square resistance and dense grid process is the key to improving conversion efficiency. In order to break through this bottleneck, a knotless screen (orthogonal screen) was developed. Although it can achieve an opening design of about 12μm, there are still horizontal mesh wires in the opening area, and the EL broken grid problem is difficult to completely avoid. For this reason, the full-opening solar cell steel plate printing technology came into being, with an opening rate of 100%, which avoids EL broken grid from the design. However, the full-opening steel plate and the silk screen screen have significant differences in material, structure and process, and the uniformity of the material is more difficult to control. In addition, the ink penetration effect is too good, which can easily lead to the extrusion of the fine grid slurry, causing poor appearance such as uneven thickness of the fine grid lines. Therefore, the fine grid slurry currently suitable for silk screen screens cannot be directly used for full-opening screens, and the materials and formulations need to be optimized.

[0003] Chinese invention patent CN111524638B discloses a crystalline silicon solar cell and its front main grid electrode silver paste and preparation method. The crystalline silicon solar cell comprises: spherical silver powder A, spherical silver powder B, flaky silver powder, glass powder, additives and adhesive; the tap density of spherical silver powder A is 4.5-7.5g / cm 3 ; The tap density of spherical silver powder B is 2.0-3.5g / cm 3 ; Glass powder includes: Pb, Si, Ti, Bi, Cu, Mn, B, Mg, W, Ca, Zn, Li, Na and K; The preparation method of the front main grid electrode silver paste is used to prepare the front main grid electrode silver paste. The crystalline silicon solar cell uses screen printing to print the above-mentioned front main grid electrode silver paste on the silicon wafer as the main grid electrode. The main grid electrode silver paste can improve the conductivity and peel strength of the product by combining spherical silver powder A, spherical silver powder B and flaky silver powder with specific particle size and specific tap density, and is matched with glass powder. However, there are network knots, which can easily lead to problems such as blockage and EL broken grid, affecting production capacity, yield and conversion efficiency. Summary of the invention

[0004] The first aspect of the present invention provides a solar cell fine grid slurry, the components of which include: metal powder, glass powder, organic carrier, plasticizer and organic additive, the metal powder is added in an amount of 80-95wt% in the fine grid slurry, the metal powder includes nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1: (3-10).

[0005] The present application has found that the amount of metal powder added to the fine grid slurry is 80-95wt%, and the metal powder includes nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1: (3-10), which can further balance the ink permeability of the fine grid slurry when printing on a fully-opened steel plate. In order to solve the problem that the fully-opened steel plate has a very good ink permeability and is prone to flooding during the printing process, the ink permeability of the fine grid slurry must be reduced to match the fully-opened steel plate to achieve the best use effect. In order to design a fine grid slurry with an ink permeability effect suitable for fully-opened steel plates, a specific compound of micron silver powder and nano silver powder, and a smaller particle size of metal powder in the fine grid slurry can improve the thixotropy of the slurry, and the improved thixotropy can effectively reduce its ink permeability effect.

[0006] Preferably, the metal powder is added to the fine grid slurry in an amount of 85-95 wt %, and the metal powder includes nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1:(3-8).

[0007] Further preferably, the amount of the metal powder added to the fine grid slurry is 86-92wt%, the metal powder includes nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1:(4-8).

[0008] The nano silver powder has a D50 particle size of 0.1-0.8 μm, a D100 particle size of 0.3-1.5 μm, and a specific surface area of ​​0.8-1.2 m 2 / g.

[0009] Preferably, the nano silver powder has a D50 particle size of 0.15-0.4 μm, a D100 particle size of 0.3-1.2 μm, and a specific surface area of ​​0.9-1.2 m 2 / g.

[0010] More preferably, the nano silver powder has a D50 particle size of 0.25 μm, a D100 particle size of 0.95 μm, and a specific surface area of ​​1.05 m 2 / g;

[0011] The micron silver powder has a D50 particle size of 0.8-2 μm, a D100 particle size of 3-5 μm, and a specific surface area of ​​0.1-0.7 m 2 / g.

[0012] Preferably, the D50 particle size of the micron silver powder is 0.85-1.1 μm, the D100 particle size is 3-4 μm, and the specific surface area is 0.3-0.7 m 2 / g.

[0013] Further preferably, the D50 particle size of the micron silver powder is 1.05 μm, the D100 particle size is 3.94 μm, and the specific surface area is 0.52 m 2 / g.

[0014] The organic carrier is composed of resin and solvent; the resin accounts for 0.45-1.5wt% of the total amount of the fine grid slurry, and the solvent accounts for 3-7.5wt% of the total amount of the fine grid slurry.

[0015] Preferably, the mass ratio of the resin to the solvent is 1:(4-10).

[0016] Further preferably, the mass ratio of the resin to the solvent is 1:(5-7).

[0017] The D100 particle sizes of the metal powder and the glass powder are both lower than 4.5 μm.

[0018] Preferably, the D100 particle size of the metal powder and the glass powder is 1-4 μm.

[0019] Further preferably, the D100 particle size of the glass powder includes one of the following: 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, and 4 μm.

[0020] Preferably, the resin includes at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin and acrylic resin.

[0021] Preferably, the solvent includes at least one of diethylene glycol butyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

[0022] Preferably, the plasticizer accounts for 0.5-4.5wt% of the total amount of the fine grid slurry, and the plasticizer includes at least one of dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, dioctyl terephthalate, tributyl citrate, acetyl tributyl citrate, and benzyl benzoate.

[0023] Preferably, the plasticizer accounts for 0.5-2.5 wt % of the total amount of the fine grid slurry.

[0024] The organic additive accounts for 0.1-1 wt % of the total amount of the fine grid slurry, and the organic additive includes a dispersant and a thixotropic agent.

[0025] Preferably, the dispersant has a dual ion and a long hydrophobic chain.

[0026] Preferably, the dispersant comprises TDO, and the thixotropic agent comprises polyamide wax.

[0027] More preferably, the dispersant is of the type DUOMEEN TDO (Akzo Nobel), and the thixotropic agent is of the type DISPARLON 6500 (Di Si Ba Long).

[0028] Preferably, the weight ratio of the dispersant to the thixotropic agent is 1:(0.3-0.8).

[0029] A second aspect of the present invention provides a method for preparing a solar cell fine grid slurry, comprising the following steps:

[0030] The metal powder, glass powder, organic carrier, plasticizer and organic additive are mixed, stirred once (15-50 r / min), allowed to stand, stirred twice (50-150 r / min), and vacuumed for degassing to obtain a first mixture;

[0031] grinding the first mixture to obtain a second mixture;

[0032] The second mixture is filtered, stirred, and then vacuumed for degassing to obtain the product.

[0033] Preferably, the fineness of the second mixture is less than 5 μm.

[0034] A third aspect of the present invention provides an application of a solar cell fine grid paste for full-opening steel plate printing.

[0035] Beneficial Effects

[0036] 1. By limiting the D100 particle size of metal powder and glass powder to less than 4.5μm, the fine grid slurry can be smoothly printed when the full-opening steel plate design opening is 10μm.

[0037] 2. The amount of metal powder added to the fine grid slurry is 80-95wt%, and the metal powder includes nano silver powder and micron silver powder, and the weight ratio of the nano silver powder to the micron silver powder is 1: (3-10), which can further balance the ink penetration effect of the fully open steel plate printing, and solve the problem of flooding in the printing process due to the good ink penetration effect of the fully open steel plate.

[0038] 3. The solvent accounts for 3-7.5wt% of the total amount of the fine grid slurry and the solvent includes at least one of diethylene glycol butyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, which can solve the problem of poor material laying caused by the mirror surface of the fully open steel plate and reduce the number of EL broken grids.

[0039] 4. The organic carrier is composed of resin and solvent; the resin accounts for 0.45-1.5wt% of the total amount of the fine grid slurry, and the resin is selected from at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin and acrylic resin, which can further improve the viscosity of the fine grid slurry and effectively reduce its ink penetration effect.

[0040] 5. The solar cell fine grid paste prepared in the present application can effectively improve the aspect ratio of the paste grid line electrode, reduce the grid line width and thus reduce the shading area, while improving the EL grid break. DETAILED DESCRIPTION

[0041] Example 1

[0042] A solar cell fine grid slurry comprises metal powder, glass powder, organic carrier, plasticizer and organic auxiliary agent.

[0043] The metal powder is nano silver powder and micron silver powder; the nano silver powder accounts for 10wt% of the total amount of the fine grid slurry, and its D50 particle size is 0.25μm, D100 particle size is 0.95μm, and its specific surface area is 1.05m 2 / g; the micron silver powder is 79wt% of the total amount of fine grid slurry, its D50 particle size is 1.05μm, D100 particle size is 3.94μm, and its specific surface area is 0.52m 2 / g;

[0044] The glass powder accounts for 2.0wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.74μm and D100 particle size is 4.23μm;

[0045] The organic vehicle is composed of resin and solvent; the resin accounts for 1.0 wt % of the total amount of the fine grid slurry; and the solvent accounts for 7.0 wt % of the total amount of the fine grid slurry.

[0046] The resins, calculated based on the total amount of the fine grid slurry, include 0.15 wt % of ethyl cellulose, 0.2 wt % of cellulose acetate butyrate, 0.05 wt % of polyvinyl butyral resin, and 0.6 wt % of acrylic resin.

[0047] The solvent, calculated based on the total amount of the fine grid slurry, comprises 1 wt % of diethylene glycol butyl ether, 0.5 wt % of diethylene glycol dibutyl ether, 4 wt % of diethylene glycol butyl ether acetate, 1 wt % of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and 0.5 wt % of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

[0048] The plasticizer accounts for 0.5wt% of the total amount of the fine grid slurry, specifically: 0.3wt% of dimethyl phthalate, 0.1wt% of acetyl tributyl citrate, and 0.1wt% of benzyl benzoate.

[0049] Based on the total amount of the fine grid slurry, the organic auxiliary agent is composed of 0.3 wt % of a dispersant and 0.2 wt % of a thixotropic agent, the dispersant model is DUOMEEN TDO (Akzo Nobel), and the thixotropic agent model is DISPARLON 6500 (DISPARLON).

[0050] The method for preparing the organic carrier comprises: mixing the resin and the solvent weighed in proportion uniformly, keeping warm at 60° C. and stirring for 90 minutes until the resin is completely and uniformly dissolved in the solvent, and naturally cooling to obtain the organic carrier.

[0051] A method for preparing fine grid slurry for solar cells:

[0052] (1) Weigh metal powder, glass powder, organic carrier, plasticizer and organic additive according to proportion and add them into the material barrel of the double planetary mixer; (2) Stir the mixture at 30 r / min for 15 min using the double planetary mixer, let it stand for more than 120 min, and then stir it at 100 r / min for 45 min. During the fast stirring process, vacuum is drawn to degassing; (3) Grind the fully stirred mixture on a three-roll mill for 5 times to a fineness of 5 μm; (4) Filter the ground mixture with a 500-mesh stainless steel wire mesh; (5) Stir the filtered mixture again at a low speed for 15 min using the double planetary mixer, vacuum is drawn to degassing during the stirring process, and finally canned to obtain a fine grid slurry.

[0053] Example 2

[0054] A solar cell fine grid slurry comprises metal powder, glass powder, organic carrier, plasticizer and organic auxiliary agent.

[0055] The metal powder is nano silver powder and micron silver powder; the nano silver powder accounts for 15wt% of the total amount of the fine grid slurry, and its D50 particle size is 0.25μm, D100 particle size is 0.95μm, and its specific surface area is 1.05m 2 / g; the micron silver powder is 74wt% of the total amount of fine grid slurry, its D50 particle size is 1.05μm, D100 particle size is 3.94μm, and its specific surface area is 0.52m2 / g;

[0056] The glass powder accounts for 2.0wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.74μm and D100 particle size is 4.23μm;

[0057] The organic vehicle is composed of resin and solvent; the resin accounts for 1.0 wt % of the total amount of the fine grid slurry; and the solvent accounts for 7.0 wt % of the total amount of the fine grid slurry.

[0058] The resins, calculated based on the total amount of the fine grid slurry, include 0.15 wt % of ethyl cellulose, 0.2 wt % of cellulose acetate butyrate, 0.05 wt % of polyvinyl butyral resin, and 0.6 wt % of acrylic resin.

[0059] The solvent, calculated based on the total amount of the fine grid slurry, comprises 1 wt % of diethylene glycol butyl ether, 0.5 wt % of diethylene glycol dibutyl ether, 4 wt % of diethylene glycol butyl ether acetate, 1 wt % of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and 0.5 wt % of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

[0060] The plasticizer accounts for 0.5wt% of the total amount of the fine grid slurry, specifically: 0.3wt% of dimethyl phthalate, 0.1wt% of acetyl tributyl citrate, and 0.1wt% of benzyl benzoate.

[0061] Based on the total amount of the fine grid slurry, the organic additive consists of 0.3 wt % of a dispersant and 0.2 wt % of a thixotropic agent, wherein the dispersant is DUOMEEN TDO and the thixotropic agent is DISPARLON 6500.

[0062] The method for preparing the organic carrier comprises: mixing the resin and the solvent weighed in proportion uniformly, keeping warm at 60° C. and stirring for 90 minutes until the resin is completely and uniformly dissolved in the solvent, and naturally cooling to obtain the organic carrier.

[0063] A method for preparing fine grid slurry for solar cells:

[0064] (1) Weigh metal powder, glass powder, organic carrier, plasticizer and organic additive according to proportion and add them into the material barrel of the double planetary mixer; (2) Stir the double planetary mixer at low speed for 15 minutes, let it stand for more than 120 minutes, and then stir it quickly for 45 minutes. During the rapid stirring process, vacuum is drawn to degassing; (3) Grind the fully stirred mixture on a three-roll mill for 5 times to a fineness of 5 μm; (4) Filter the ground mixture with a 500-mesh stainless steel wire mesh; (5) Stir the filtered mixture again with a double planetary mixer at low speed for 15 minutes. During the stirring process, vacuum is drawn to degassing, and finally canned to obtain a fine grid slurry.

[0065] Example 3

[0066] A solar cell fine grid slurry comprises metal powder, glass powder, organic carrier, plasticizer and organic auxiliary agent.

[0067] The metal powder is nano silver powder and micron silver powder; the nano silver powder accounts for 10wt% of the total amount of the fine grid slurry, and its D50 particle size is 0.25μm, D100 particle size is 0.95μm, and its specific surface area is 1.05m 2 / g; the micron silver powder is 79wt% of the total amount of fine grid slurry, its D50 particle size is 1.05μm, D100 particle size is 3.94μm, and its specific surface area is 0.52m 2 / g;

[0068] The glass powder accounts for 2.0wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.74μm and D100 particle size is 4.23μm;

[0069] The organic vehicle is composed of resin and solvent; the resin accounts for 1.0 wt % of the total amount of the fine grid slurry; and the solvent accounts for 6.0 wt % of the total amount of the fine grid slurry.

[0070] The resins, calculated based on the total amount of the fine grid slurry, include 0.15 wt % of ethyl cellulose, 0.2 wt % of cellulose acetate butyrate, 0.05 wt % of polyvinyl butyral resin, and 0.6 wt % of acrylic resin.

[0071] The solvent, calculated based on the total amount of the fine grid slurry, comprises 0.5 wt % of diethylene glycol butyl ether, 0.5 wt % of diethylene glycol dibutyl ether, 3 wt % of diethylene glycol butyl ether acetate, 1 wt % of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and 1 wt % of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

[0072] The plasticizer accounts for 1.5wt% of the total amount of the fine grid slurry, specifically: 0.8wt% of dimethyl phthalate, 0.2wt% of acetyl tributyl citrate, and 0.5wt% of benzyl benzoate.

[0073] Based on the total amount of the fine grid slurry, the organic additive consists of 0.3 wt % of a dispersant and 0.2 wt % of a thixotropic agent, wherein the dispersant is DUOMEEN TDO and the thixotropic agent is DISPARLON 6500.

[0074] The method for preparing the organic carrier comprises: mixing the resin and the solvent weighed in proportion uniformly, keeping warm at 60° C. and stirring for 90 minutes until the resin is completely and uniformly dissolved in the solvent, and naturally cooling to obtain the organic carrier.

[0075] A method for preparing fine grid slurry for solar cells:

[0076] (1) Weigh metal powder, glass powder, organic carrier, plasticizer and organic additive according to proportion and add them into the material barrel of the double planetary mixer; (2) Stir the double planetary mixer at low speed for 15 minutes, let it stand for more than 120 minutes, and then stir it quickly for 45 minutes. During the rapid stirring process, vacuum is drawn to degassing; (3) Grind the fully stirred mixture on a three-roll mill for 5 times to a fineness of 5 μm; (4) Filter the ground mixture with a 500-mesh stainless steel wire mesh; (5) Stir the filtered mixture again with a double planetary mixer at low speed for 15 minutes. During the stirring process, vacuum is drawn to degassing, and finally canned to obtain a fine grid slurry.

[0077] Example 4

[0078] A solar cell fine grid slurry comprises metal powder, glass powder, organic carrier, plasticizer and organic auxiliary agent.

[0079] The metal powder is nano silver powder and micron silver powder; the nano silver powder accounts for 10wt% of the total amount of the fine grid slurry, and its D50 particle size is 0.25μm, D100 particle size is 0.95μm, and its specific surface area is 1.05m 2 / g; the micron silver powder is 79wt% of the total amount of fine grid slurry, its D50 particle size is 1.05μm, D100 particle size is 3.94μm, and its specific surface area is 0.52m 2 / g;

[0080] The glass powder accounts for 2.0wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.74μm and D100 particle size is 4.23μm;

[0081] The organic vehicle is composed of resin and solvent; the resin accounts for 1.0 wt % of the total amount of the fine grid slurry; and the solvent accounts for 5 wt % of the total amount of the fine grid slurry.

[0082] The resins, calculated based on the total amount of the fine grid slurry, include 0.15 wt % of ethyl cellulose, 0.2 wt % of cellulose acetate butyrate, 0.05 wt % of polyvinyl butyral resin, and 0.6 wt % of acrylic resin.

[0083] The solvent is calculated based on the total amount of the fine grid slurry, and the content of diethylene glycol butyl ether is 1wt%, diethylene glycol butyl ether acetate is 3wt%, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate is 0.5wt%, and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate is 0.5wt%.

[0084] The plasticizer accounts for 2.5wt% of the total amount of the fine grid slurry, specifically: 0.8wt% of dimethyl phthalate, 1wt% of dioctyl phthalate, 0.2wt% of acetyl tributyl citrate, and 0.5wt% of benzyl benzoate.

[0085] Based on the total amount of the fine grid slurry, the organic additive consists of 0.3 wt % of a dispersant and 0.2 wt % of a thixotropic agent, wherein the dispersant is DUOMEEN TDO and the thixotropic agent is DISPARLON 6500.

[0086] The method for preparing the organic carrier comprises: mixing the resin and the solvent weighed in proportion uniformly, keeping warm at 60° C. and stirring for 90 minutes until the resin is completely and uniformly dissolved in the solvent, and naturally cooling to obtain the organic carrier.

[0087] A method for preparing fine grid slurry for solar cells:

[0088] (1) Weigh metal powder, glass powder, organic carrier, plasticizer and organic additive according to proportion and add them into the material barrel of the double planetary mixer; (2) Stir the double planetary mixer at low speed for 15 minutes, let it stand for more than 120 minutes, and then stir it quickly for 45 minutes. During the rapid stirring process, vacuum is drawn to degassing; (3) Grind the fully stirred mixture on a three-roll mill for 5 times to a fineness of 5 μm; (4) Filter the ground mixture with a 500-mesh stainless steel wire mesh; (5) Stir the filtered mixture again with a double planetary mixer at low speed for 15 minutes. During the stirring process, vacuum is drawn to degassing, and finally canned to obtain a fine grid slurry.

[0089] Comparative Example 1

[0090] A solar cell fine grid slurry comprises metal powder, glass powder, organic carrier and organic auxiliary agent.

[0091] The metal powder is micron silver powder; the micron silver powder accounts for 89wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.71μm, the D100 particle size is 6.78μm, and its specific surface area is 0.54m 2 / g;

[0092] The glass powder accounts for 2.0wt% of the total amount of the fine grid slurry, and its D50 particle size is 1.74μm and D100 particle size is 4.23μm;

[0093] The organic vehicle is composed of resin and solvent; the resin accounts for 1.0 wt% of the total amount of the fine grid slurry; and the solvent accounts for 7.5 wt% of the total amount of the fine grid slurry.

[0094] The resins, calculated based on the total amount of the fine grid slurry, include 0.15 wt % of ethyl cellulose, 0.2 wt % of cellulose acetate butyrate, 0.05 wt % of polyvinyl butyral resin, and 0.6 wt % of acrylic resin.

[0095] The solvent, calculated based on the total amount of the fine grid slurry, comprises 1.5 wt % of diethylene glycol butyl ether, 4.5 wt % of diethylene glycol butyl ether acetate, 1 wt % of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and 0.5 wt % of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

[0096] Based on the total amount of the fine grid slurry, the organic additive consists of 0.3 wt % of a dispersant and 0.2 wt % of a thixotropic agent, wherein the dispersant is DUOMEEN TDO and the thixotropic agent is DISPARLON 6500.

[0097] The method for preparing the organic carrier comprises: mixing the resin and the solvent weighed in proportion uniformly, keeping warm at 60° C. and stirring for 90 minutes until the resin is completely and uniformly dissolved in the solvent, and naturally cooling to obtain the organic carrier.

[0098] A method for preparing fine grid slurry for solar cells:

[0099] (1) Weigh metal powder, glass powder, organic carrier and organic additive according to proportion and add them into the material barrel of the double planetary mixer; (2) Stir the double planetary mixer at low speed for 15 minutes, let it stand for more than 120 minutes, and then stir it quickly for 45 minutes. During the rapid stirring process, vacuum is drawn to degassing; (3) Grind the fully stirred mixture on a three-roll mill for 5 times to a fineness of 5 μm; (4) Filter the ground mixture with a 500-mesh stainless steel wire mesh; (5) Stir the filtered mixture again with a double planetary mixer at low speed for 15 minutes. During the stirring process, vacuum is drawn to degassing, and finally canned to obtain a fine grid slurry.

[0100] Performance Testing Methods

[0101] The fine grid slurry prepared in the embodiment and the comparative example was printed on the surface of the cell by screen printing, and after high-temperature sintering, the front electrode of the crystalline silicon solar cell was made. (A semi-finished cell with a mainstream specification of 182*183 on the market was selected, and a steel plate with a 10um opening was used to print the fine grid slurry prepared in the embodiment and the comparative example on the surface of the semi-finished cell by screen printing to preliminarily form the electrode of the cell. The printing speed was 550mm / s, the printing pressure was 50N, the screen spacing was 1.5mm, and the return speed was 1400mm / s. Then, the semi-finished cell with the electrode printed was passed through an infrared sintering furnace and sintered at high temperature for metallization, and finally a finished crystalline silicon solar cell was made). Then, an EL tester was used to detect the number of broken grids, and a 3D laser microscope was used to perform a 3D morphology test on the fine grid of the cell to measure the height and width of the fine grid, and then the aspect ratio of the fine grid was calculated. The test data are listed in Table 1.

[0102] Performance test data

[0103] Table 1

[0104] EL gate breaking quantity Fine grid height Fine grid width Fine grid aspect ratio Example 1 0 5.55 14.84 0.37 Example 2 0 5.80 13.67 0.42 Example 3 0 5.77 14.10 0.41 Example 4 0 5.95 13.82 0.43 Comparative Example 1 2 5.25 16.64 0.32

[0105] It can be concluded from the above table that the use of the solar cell fine grid paste for full-opening steel plate printing of the present invention can effectively improve the aspect ratio of the paste grid line electrode, reduce the grid line width and thus reduce the shading area, while improving the EL break grid.

Claims

1. A solar cell fine grid slurry, characterized in that: The components include: metal powder, glass powder, organic carrier, plasticizer and organic additive. The addition amount of the metal powder in the fine grid slurry is 80-95wt%. The metal powder includes nano silver powder and micron silver powder. The weight ratio of the nano silver powder to the micron silver powder is 1: (3-10).

2. The solar cell fine grid slurry according to claim 1, characterized in that: The nano silver powder has a D50 particle size of 0.1-0.8 μm, a D100 particle size of 0.3-1.5 μm, and a specific surface area of ​​0.8-1.2 m 2 / g.

3. The solar cell fine grid slurry according to claim 2, characterized in that: The micron silver powder has a D50 particle size of 0.8-2 μm, a D100 particle size of 3-5 μm, and a specific surface area of ​​0.1-0.7 m 2 / g.

4. The solar cell fine grid slurry according to claim 1 or 3, characterized in that: The organic carrier is composed of resin and solvent; the resin accounts for 0.45-1.5wt% of the total amount of the fine grid slurry, and the solvent accounts for 3-7.5wt% of the total amount of the fine grid slurry.

5. The solar cell fine grid slurry according to claim 4, characterized in that: The D100 particle sizes of the metal powder and the glass powder are both lower than 4.5 μm.

6. The solar cell fine grid slurry according to claim 5, characterized in that: The resin includes at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin and acrylic resin.

7. The solar cell fine grid slurry according to claim 6, characterized in that: The solvent includes at least one of diethylene glycol butyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.

8. The solar cell fine grid slurry according to claim 7, characterized in that: The plasticizer accounts for 0.5-4.5wt% of the total amount of the fine grid slurry, and the plasticizer includes at least one of dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, dioctyl terephthalate, tributyl citrate, acetyl tributyl citrate, and benzyl benzoate.

9. A method for preparing a solar cell fine grid slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: The metal powder, glass powder, organic carrier, plasticizer and organic additive are mixed, stirred once and allowed to stand, stirred twice, and vacuumed for degassing to obtain a first mixture; grinding the first mixture to obtain a second mixture; The second mixture is filtered, stirred, and then vacuumed for degassing to obtain the product.

10. An application of the solar cell fine grid slurry according to any one of claims 1 to 8, characterized in that: Used for full-opening steel plate printing.

Citation Information

Patent Citations

  • A crystalline silicon solar cell, its front main grid electrode silver paste, and its preparation method

    CN111524638B